Risk of premature birth, low apgar score and low birth weight for teenage births. (7th June 2011) - Watts, K; Collier, J; Fraser, D
Abstract : Background: Previous research on neonatal outcomes in teenage women has focused on primiparous or multiparous teenagers separately thus failing to examine outcomes for all teenager groups. This study has addressed this shortfall. Aim: To compare three neonatal birth outcomes: between teenagers (primiparous and multiparous) and women aged 20–25 years; between primiparous and multiparous teenagers; and between multiparous teenagers having a rapid repeat birth (≤18 months) and those not. Methodology: After gaining ethical approval, a retrospective cohort study using secondary analysis of hospital episode data was undertaken on 32 895 births to women aged <26 over a 10 year period in two UK maternity units. Data were analysed using logistic regression models. Key Findings: In the primiparous populations teenagers had an increased risk of ↓Apgar Score than women aged 20–25 years, but a reduced risk of premature birth. However, in the multiparous populations teenagers had an increased risk of premature birth. For teenagers, multiparous teenagers had an increased risk of premature birth but a reduced risk of low Apgar Score and low birth weight than primiparous teenagers. Rapid repeat births in teenagers increased the risk of a premature birth further. Implications for practice: Care pathways for teenagers should be tailored for initial or for subsequent births. Additional surveillance during labour is required for primiparous teenagers due to the risk of low Apgar Score. For multiparous teenagers premature birth remains an increased risk and closer monitoring is required.